1992
DOI: 10.1177/0963689792001002-305
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Safety, and Efficacy of Myoblast Transfer Therapy on Duchenne Muscular Dystrophy Boys

Abstract: Five billion normal myoblasts were injected into each of 21 Duchenne muscular dystrophy (DMD) boys aged 6-14 yr to assess the feasibility, safety, and efficacy of the Phase II myoblast transfer therapy (MTT). The Phase II study was designed to strengthen muscles of both lower limbs. Forty-eight intramuscular injections transferred the myoblasts into 22 major muscles at 55.6 x 10(6)/mL in 10 min under general anesthesia. Eleven boys had received 8 million myoblasts each 1 yr ago in the Phase I MTT. In the Phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…In spite of this success, the subsequent myoblast transplantation performed on DMD boys was unsuccessful (Law et al 1992;Mendell et al 1995;Tremblay et al 1993). In this section, we discuss the problems of myoblast-transplantation and other cell sources for cell therapy of DMD.…”
Section: Cell Therapy For Dmdmentioning
confidence: 99%
“…In spite of this success, the subsequent myoblast transplantation performed on DMD boys was unsuccessful (Law et al 1992;Mendell et al 1995;Tremblay et al 1993). In this section, we discuss the problems of myoblast-transplantation and other cell sources for cell therapy of DMD.…”
Section: Cell Therapy For Dmdmentioning
confidence: 99%
“…Mendell et al (Mendell et al, 1995) injected myoblast, once a month for six months, in 12 DMD patients, but this treatment failed to improve strength. Law et al (Law et al, 1992) demonstrated the feasibility and safety of myoblast transplantation, but with a poor clinical improvement. At the end of the 90's, a careful overview of the previous initial trials brought several research teams to identify three problems responsible for the limited results observed: (1) 3 days after the graft, at least 75% of the transplanted myoblasts died (Fan et al, 1996;Guerette et al, 1997;Huard et al, 1994); (2) myoblasts were not able to migrate more than 200 μm away from the intramuscular injection trajectory (Skuk et al, 1999); (3) if immunosuppression was not adequate, the myoblasts were rapidly rejected in less than 2 weeks (Guerette et al, 1994) or were induced to activate apoptosis, such as cyclophosphamide usage (Hardiman et al, 1993;Hong et al, 2002).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Lot release testing consisted of sterility, endotoxin, mycoplasma, and testing for myoblast identity, purity, potency, viability, and cell count on a pooled sample prior to transplant meeting quality control standards [17]. A retain sample of myoblasts was frozen in liquid nitrogen from each transplant.…”
Section: Preparation Of Myoblastsmentioning
confidence: 99%
“…Random samples of the myoblasts were tested for their ability to divide, fuse, and form myotubes [17]. Lot release testing consisted of sterility, endotoxin, mycoplasma, and testing for myoblast identity, purity, potency, viability, and cell count on a pooled sample prior to transplant meeting quality control standards [17].…”
Section: Preparation Of Myoblastsmentioning
confidence: 99%
See 1 more Smart Citation